2020
DOI: 10.3126/jafu.v4i1.47061
|View full text |Cite
|
Sign up to set email alerts
|

Mulching materials affect growth and yield characters of cucumber (Cucumis sativus cv. Malini) under drip irrigation condition in Chitwan, Nepal

Abstract: An experiment was done to evaluate the effect of mulching materials on growth and yield characters of cucumber (var: Malini) under drip irrigation condition during February to May 2018 in Chitwan district, Nepal. The experiment was done by using Randomized Complete Block Design (RCBD). Accordingly, four different mulching materials, viz. silver on black polyethylene mulch, black polyethylene mulch, rice straw mulch, and rice husk mulch were used as treatments. Each treatment was replicated four times. Un-mulch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 11 publications
0
5
0
Order By: Relevance
“…Farmers who marketed their product directly to customers received a bigger share of the consumer's price while those who marketed their produce through agent (Karki et al, 2020).…”
Section: Whom To Sellmentioning
confidence: 99%
“…Farmers who marketed their product directly to customers received a bigger share of the consumer's price while those who marketed their produce through agent (Karki et al, 2020).…”
Section: Whom To Sellmentioning
confidence: 99%
“…Tomar et al, 2018 found that tomato grown with bio-mulch produces the maximum number of flowers/inflorescence and number of inflorescence per plant. While in cucumber the highest number of male (69.50) and female (33.50) flowers per plant were recorded in silver on black polyethylene mulch used (Karki et al, 2020). 3).…”
Section: Resultsmentioning
confidence: 94%
“…The mulch materials influence the number of flowers also reduce the number of days to flower as well as have a positive effect on the fruit set (Kumar & Verma, 2009;Iqbal et al, 2009;Ahmad et al, 2011;Marichamy et al, 2016;Verma et al, 2016;Tomar et al, 2018;Molla et al, 2019;Debbarma et al, 2019). Many studies also reported an increment in the early and total yield of vegetables grown on different mulching materials (Ibarra-Jimenez et al, 2004;Kumar and Verma, 2009;Molla et al, 2019;Debbarma et al, 2019;Karki et al, 2020;Bogevska et al, 2021;Adamović et al, 2021). Yield can be improved by using mulches in vegetables from 17.39% in chili peppers to 60.74% in broccoli (Ray & Biswasi, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…According to (Dutta, 2006) significantly higher plant height was observed under polythene mulched groundnut. Similarly, silver on black polythene mulch treatment and black polythene mulch treatment in cucumber recorded higher plant heights over rice straw and rice husk mulch treatments (Karki et al, 2020). L. camara is very good source of protein with the value of 24.84±0.51(%)…”
Section: Effect Of Mulching On Plant Heightmentioning
confidence: 89%